2012
DOI: 10.1080/09540105.2011.583228
|View full text |Cite
|
Sign up to set email alerts
|

Application of enzyme-linked immunosorbent assay for the assessment of spring wheat quality

Abstract: The present project was undertaken with the key objective to find out relationship of HMW and LMW glutenin sub-units and immunological test with bread making quality. The antibody response assessed through animal modelling by using rabbits as test animals showed significant variation towards high molecular weight glutenin (HMG) and low molecular weight glutenin (LMG) of different spring wheat varieties. A significant and positive relationship of bread sensory attributes with antibody response against HMG was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 18 publications
4
6
0
Order By: Relevance
“…Andrews, Blundell, and Skerritt (1993) investigated correlations between antibody binding and dough strength parameters by using antibodies specific for LMW-GS and found similar kind of relationship among some quality parameters. Our results are also in consistent with the findings of Khan et al (2011) who reported that anti-LMG antibody response was found negatively correlated to total scores of breads and chapattis. The anti-HMG antibody response was found positively correlated to total scores of breads and chapattis.…”
Section: Correlation Studiessupporting
confidence: 96%
See 1 more Smart Citation
“…Andrews, Blundell, and Skerritt (1993) investigated correlations between antibody binding and dough strength parameters by using antibodies specific for LMW-GS and found similar kind of relationship among some quality parameters. Our results are also in consistent with the findings of Khan et al (2011) who reported that anti-LMG antibody response was found negatively correlated to total scores of breads and chapattis. The anti-HMG antibody response was found positively correlated to total scores of breads and chapattis.…”
Section: Correlation Studiessupporting
confidence: 96%
“…Li et al (2008) suggested that the polyclonal antibodies are the useful tools for rapid prediction and screening of wheat quality. Khan et al (2011) also reported significant variation in antibody response toward HMW-GS and low molecular weight glutenin subunits (LMW-GS) of different wheat varieties which supports to the present results in which significant variation observed among wheat varieties due to antibody response toward HMW-GS and LMW-GS. The antibody response against HMW-GS varied from 0.300 to 0.70 among different wheat varieties.…”
Section: Antibody Response Against Omega Gliadinsupporting
confidence: 94%
“…Anti-HMG antibody response was positively correlated to total scores of breads and chapattis. Anti-HMG antibody can be employed as a means for screening wheat for better quality chapattis and breads (Khan et al, 2011).…”
Section: Immunochemical Characteristics Of Grain Gluteninmentioning
confidence: 99%
“…However, immunological analysis is still the most common rapid method for screening a large number of samples, due to its low-cost and high throughput. Based on ELISA, AFB 1 presence in feed, cereals were screened with high sensitivity (Khan et al, 2012;Rossi et al, 2012). Based on ELISA, AFB 1 presence in feed, cereals were screened with high sensitivity (Khan et al, 2012;Rossi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Ye carried out latex agglutination tests based on antibody against AFB 1 and the method was successfully applied in the detection of peanut or rice samples (Ye et al, 2011). Based on ELISA, AFB 1 presence in feed, cereals were screened with high sensitivity (Khan et al, 2012;Rossi et al, 2012). Li developed ELISA experiments to detect AFB 1 with a high sensitivity (visual limit of detection of 0.03 ng mL À1 ) and he explained the potential mechanism of the binding between antibody and AFB 1 using homology modelling and molecular docking (Li et al, 2012).…”
Section: Introductionmentioning
confidence: 99%